Spontaneous Renal Cholesterol Crystal Embolism In A Patient with Functionally Solitary Kidney. Issue 2 (April 2014) - Celik, Kenan; Sumnu, Abdullah; Gursu, Meltem; Sakin, Abdullah; Uzun, Sami; Ozturk, Savas; Kazancioglu, Rumeyza
No abstract available